The potential contribution of riparian vegetation in non-point source pollution control during rainfall events in a tropical urban watershed - Cecilia Loretti de Paiva; João Miguel Merces Bega; Karen Tavares Zambrano; Davi Gasparini Fernandes Cunha (Revista Brasileira de Recursos Hídricos)
ABSTRACT The presence of riparian vegetation can reduce the transport of sediments into receiving water bodies from surface runoff during rainfall events. However, this process is still overlooked in tropical watersheds, limiting the capacity of managers and decision-makers to implement control measurements of non-point pollution sources. This study evaluated suspended solids concentrations in a predominantly urban tropical stream near its outlet during stormflow conditions. It also examined how the structure and conservation of riparian vegetation in the immediate surrounding of an urban stream reach likely influenced the patterns of inputs of such non-point source pollutants. Four rainfall events with distinct hydrological characteristics were studied. Event Mean Concentrations (EMCs) and Mass versus Volume [M(V)] curves were obtained for all the monitored events. Two Rapid Assessment Protocols (RAPs) were used to assess the structure and conservation status of riparian vegetation along the urban stream reach. The lack of an adequate riparian vegetation buffer was found to exacerbate soil loss due to erosion. Direct surface runoff generated within the watershed showed a high potential for pollution, with evidence of non-point source pollution and first-flush effects observed during rainfall events with lower intensity. These findings are expected to contribute to the ongoing discussion on urban forestry and riparian zone reforestation, supporting the development of strategies aimed at mitigating non-point source pollution.